2020
DOI: 10.24264/lfj.20.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Production Optimization of Keratinase from Three Bacillus Strains

Abstract: Indonesia has large coastal areas. The fisheries are good for exploitation. In the previous studies, bacteria producing keratinase were isolated from fish market waste. Keratinase enzyme is able to degrade keratin on the skin. Enzyme activity is influenced by external conditions, such as pH, temperature, and incubation time. The study aimed to investigate the characteristics and the optimal conditions of the keratinase production. The materials used were keratinase from three Bacillus strains: Bacillus thuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Principal component analysis (PCA) is a statistical technique used to consolidate several indices into a single aggregated measure that enables the reduction of variables, assesses the correlation between variables, and visualizes data (Wibowo and Yuliatmo, 2020;Yuliatmo et al, 2021). Thus, reducing the number of variables entails transforming the original collection of variables into a new set of principal components, which are smaller in number (Łojewski et al, 2014).…”
Section: Principal Component Analysis On Leather Physical Qualitymentioning
confidence: 99%
“…Principal component analysis (PCA) is a statistical technique used to consolidate several indices into a single aggregated measure that enables the reduction of variables, assesses the correlation between variables, and visualizes data (Wibowo and Yuliatmo, 2020;Yuliatmo et al, 2021). Thus, reducing the number of variables entails transforming the original collection of variables into a new set of principal components, which are smaller in number (Łojewski et al, 2014).…”
Section: Principal Component Analysis On Leather Physical Qualitymentioning
confidence: 99%
“…The catch is dried, fermented, salted, boiled, or smoked in various proportions, with 46% consumed fresh from the fish market (FAO, 2019). Wibowo et al (2017b) identified the bacteria that produce keratinase from fish market waste, which was later described and optimized by Wibowo and Yuliatmo (2020). This enzyme is employed in the hair removal (unhairing) procedure for eco-friendly fish skin tanning.…”
Section: Introductionmentioning
confidence: 99%